Functional specialization among members of knickkopf family of proteins in insect cuticle organization. - Chaudhari, Sujata S.; Moussian, Bernard; Specht, Charles A.; Arakane, Yasuyuki; Kramer, Karl J.; Beeman, Richard W.; Muthukrishnan, Subbaratnam (My University, 2014)
Our recent study on the functional analysis of the Knickkopf protein from T. castaneum (TcKnk), indicated a novel role for this protein in protection of chitin from degradation by chitinases. Knk is also required for the laminar organization of chitin in the procuticle. During a bioinformatics search using this protein sequence as the query, we discovered the existence of a small family of three Knk-like genes (including the prototypical TcKnk) in the T. castaneum genome as well as in all insects with completed genome assemblies. The two additional Knk-like genes have been named TcKnk2 and TcKnk3. Further complexity arises as a result of alternative splicing and alternative polyadenylation of transcripts of TcKnk3, leading to the production of three transcripts (and by inference, three proteins) from this gene. These transcripts are named TcKnk3-Full Length (TcKnk3-FL), TcKnk3-5′ and TcKnk3-3′. All three Knk-family genes appear to have essential and non-redundant functions. RNAi for TcKnk led to developmental arrest at every molt, while down-regulation of either TcKnk2 or one of the three TcKnk3 transcripts (TcKnk3-3′) resulted in specific molting arrest only at the pharate adult stage. All three Knk genes appear to influence the total chitin content at the pharate adult stage, but to variable extents. While TcKnk contributes mostly to the stability and laminar organization of chitin in the elytral and body wall procuticles, proteins encoded by TcKnk2 and TcKnk3-3′ transcripts appear to be required for the integrity of the body wall denticles and tracheal taenidia, but not the elytral and body wall procuticles. Thus, the three members of the Knk-family of proteins perform different essential functions in cuticle formation at different developmental stages and in different parts of the insect anatomy.
Citation: Chaudhari SS, Moussian B, Specht CA, Arakane Y, Kramer KJ, Beeman RW, et al. (2014) Functional Specialization Among Members Of Knickkopf Family Of Proteins In Insect Cuticle Organization. PLoS Genet 10(8): e1004537. doi:10.1371/journal.pgen.1004537
Keywords: Adults; Chitin; Complementary DNA; Insects; Larvae; Pupae; RNA extraction; Reverse transcriptase-polymerase chain reaction